Psychometrics of the screen for adult anxiety related disorders (SCAARED)- A new scale for the assessment of DSM-5 anxiety disorders. (July 2017) - Angulo, Melina; Rooks, Brian T.; Gill, MaryKay; Goldstein, Tina; Sakolsky, Dara; Goldstein, Benjamin; Monk, Kelly; Hickey, Mary Beth; Diler, Rasim S.; Hafeman, Danella; Merranko, John; Axelson, David; et al.
Abstract: Objective: To examine the psychometrics of the Screen for Adult Anxiety Related Disorders (SCAARED). Methods: The SCAARED was adapted from the Screen for Child Anxiety Related Emotional Disorders. Participants (N=336) ages 18–27 years old were evaluated using the Structured Clinical Interview for DSM-IV Disorders (SCID). The SCAARED was completed at or within two-weeks before the SCID. The psychometrics of the SCAARED were analyzed using standard statistical analyses including principal components, and Receiver Operant Curve analyses. A replication was performed in an age/sex matched independent sample (N=158). Results: The SCAARED showed four factors: somatic/panic/agoraphobia, generalized anxiety, separation anxiety, and social anxiety. The total and each factor scores demonstrated good internal consistency (α=0.86−0.97) and good discriminant validity between anxiety and other disorders and within anxiety disorders for generalized and social anxiety. Area Under the Curve for the total and each of the factor scores ranged between 0.72 and 0.84 (p<0.0001). These results were replicated in the independent sample. Conclusions: The SCAARED showed excellent psychometric properties supporting its use to screen adults for anxiety disorders, longitudinal studies following youth into adulthood and studies comparing child and adult populations. Further replication studies in larger community and clinical samples are indicated. Highlights: The Screen for Adult Anxiety Related Disorders (SCAARED) showed excellent psychometrics. It has four factors: somatic/panic/agoraphobia, generalized anxiety, separation anxiety, and social anxiety that are useful to screen for the respective anxiety disorders. Together with its child counterpart, it can also be use for longitudinal studies following youth into adulthood and studies comparing child and adult populations. Further replication studies in larger community and clinical samples are indicated.